Quality of life of patients with cancer attending outpatient clinics at the King Abdulaziz Medical City, Riyadh, Saudi Arabia - Sultan Mohammed Alshehri; Abdulrhman Faeq Alzamil; Rayan Ibrahim Alturki; Humoud Auoad Alhoraim; Riyadh Ali Alghamdi; Mohammed Salman Almutairi; Emad Mohammad Masuadi; Abdullah Mohammed Algarni (Wolters Kluwer Medknow Publications, 2020)
Introduction: Measurement of quality of life (QoL) can be an important tool for the comprehensive care of the patients. This study was designed to assess the QoL of patients with cancer attending outpatient clinics at the King Abdulaziz Medical City, Riyadh, Saudi Arabia, and examined its association with sociodemographic variables and also identified the worst type of cancer. Materials and Methods: This cross-sectional study involved 178 participants who met the selection criteria: adult Saudi patients (≥18 years) who had been diagnosed with cancer, were documented in the health care system, and were cognitively able to answer the questionnaire. Those who underwent any surgical, hormonal, radiation, or chemotherapy within 2 weeks were excluded from the study. Patients are recruited by nonprobability convenience sampling between December 20, 2017, and January 1, 2018. Data were obtained using an Arabic version of the European Organisation for Research and Treatment of Cancer (EORTC) QoL Questionnaire (QLQ)-C30 developed, translated, and validated by the EORTC. QLQ-C30 measures three domains: functional, symptoms, and global QoL. Results: The younger (≤29 years) the patients, the better their global QoL. Women had a trend to score worse in all domains but only statistically significant in dyspnea (P < 0.05). Furthermore, patients with high school education and higher exhibited better physical function (PF) than illiterate patients. Multivariate analysis revealed gastric cancer as the most distressing cancer in terms of global QoL (P < 0.01), whereas patients with hematologic and genitourinary cancers trended high scores but insignificant. Moreover, patients with Stage I-II disease had better scores for PF, role function, social function, and anorexia compared with Stage III-IV disease. Conclusion: The QoL of cancer patients is a useful barometer of their overall health. It can also indicate the impact of different types of cancer on QoL. Sociodemographic variables, such as age, gender, level of education, diagnosis, and stage, can affect the QoL of cancer patients.